PENDIDIKAN KARAKTER: SOLUSI MENGATASI KRISIS MORAL BANGSA - Bambang Suryadi (Nizham Jurnal Studi Keislaman, 2015)
One of the most challanging problems of our nation is mocal decadence and this problem needs to be solve urgently. There are many factors that lead to the moral decadence, among those factors are inconsistence in law enforcement, lack of role model, reduced role of parents and teachres, and inconducive environment. Given the fact of moral decadence, the government has made an effort in moral education or character building. This effort cannot be solely done by single authority or party, rather it need wider engagement and comprehensive involvement from all stakeholders. Using this method and strategy, it is expected that moral education or character building may succeed. In the context of family education and school, parents and teachers play very significant roles in moral education and character building. This paper aims at revitalizing the roles of parents and teachers in inculcating moral values for our children through family education and school education.